2013
DOI: 10.3109/09273948.2013.854392
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidisEndogenous Endophthalmitis with Meningitis in an Immunocompetent Child

Abstract: Neisseria meningitidis is a major cause of childhood morbidity and mortality worldwide. We describe an exceptional case of an immunocompetent 15-month-old child presenting with a unilateral anterior uveitis, hypopyon, and sepsis. Anterior chamber aspirate demonstrated gram-negative cocci before Neisseria meningitidis was identified in blood and cerebrospinal fluid. Meningococcal endophthalmitis presents variably with sepsis, meningitis, or isolated ocular symptoms. Diagnosis is a clinical challenge, requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although Pappuru et al have observed a better outcome in patients who received corticosteroids [ 4 ], the 11 patients in our review that were treated with corticosteroids did not present a lower rate of complications. Moreover, local administration of corticosteroids could be harmful as it could delay the diagnostic [ 5 ] and interfere with local antimicrobials in case of intravitreal administration, and it could also make the patient more vulnerable to fungal infection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pappuru et al have observed a better outcome in patients who received corticosteroids [ 4 ], the 11 patients in our review that were treated with corticosteroids did not present a lower rate of complications. Moreover, local administration of corticosteroids could be harmful as it could delay the diagnostic [ 5 ] and interfere with local antimicrobials in case of intravitreal administration, and it could also make the patient more vulnerable to fungal infection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is remarkable that, although Neisseria meningitidis type B is the most common type in meningococcal infection [ 5 ], type C is present in the majority of reviewed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Meningococcal endophthalmitis presents variably with sepsis [102,112,113,121], meningitis [114,115], or isolated ocular symptoms without systemic illness [112,[116][117][118][119], although subsequent development of other expressions of meningococcal disease should not be ruled out [103][104][105]. Thus, delayed or incorrect treatment of meningococcal ocular infections ultimately risks blindness, disability, or death [120] (Table 1).…”
Section: Meningococcal Ophthalmiamentioning
confidence: 99%
“…Ocular microbial infections are caused by a variety of pathogenic microorganisms such as fungi [ 6 , 7 , 33 ], viruses [ 20 , 34 , 35 ], parasites [ 36 , 37 , 38 ] and bacteria [ 39 , 40 , 41 ]. These microbes reach the inner eyes following intraocular surgery [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], trauma [ 49 , 50 ], or access by the metastatic spread from other affected anatomical regions [ 39 , 51 , 52 , 53 , 54 , 55 , 56 ] and give rise to different effects in patients according to the virulence of microorganisms and the patient immune status [ 22 , 23 , 57 , 58 , 59 , 60 ]. The primary symptoms of these infections damaging the inner eyes is blurred vision and rapidly deteriorating visual acuity within a few days of infections [ 8 , 9 ].…”
Section: Challenges Of Conventional Antimicrobial Treatments For Omentioning
confidence: 99%
“…Bacteria such as Enterococci [ 120 ], Staphylococci [ 44 , 47 , 96 ] and Bacilli [ 68 , 121 ] are common cause of infectious diseases in the eyes. Among all, Staphylococcus aureus , Bacillus cereus and gram-negative bacteria, such as Escherichia coli , Neisseria meningitides and Klebsiella species are responsible for endogenous retinal infections spread from other anatomical area [ 6 , 39 , 40 , 51 , 56 ]. For instance, drug abusers may contract Bacillus infection from contaminated drug taken intravenously or from injection paraphernalia [ 52 ].…”
Section: Challenges Of Conventional Antimicrobial Treatments For Omentioning
confidence: 99%